PENGEMBANGAN TALENT MANAGEMENT UNTUK MEMBENTUK KOMITMEN ORGANISASI : (STUDI KASUS PADA PT BANK MEGA Tbk. SEMARANG DIVISI CARD COLLECTION) - Sekar Widyasari Putri; Bulan Prabawani; Hari Susanta Nugraha (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Organizational commitment to individual talent is important to ensure that the organization has future candidates. The problem of employee turnover needs special attention from the company because it is an indicator of low organizational commitment. Turnover fluctuations during 2016 - 2018 at PT. Bank Mega Semarang showed an increase in the past year. The purpose of this study is to find out how talent management practices are and how the results of talent management are developed to shape organizational commitment at PT. Bank Mega Semarang, card collection division. This study uses a qualitative method with a type of descriptive research that describes the practice of Talent Management. Data collection techniques with interview methods (unstructured), observation and document analysis. The Talent Management model which consists of four stages, namely Talent Acquisition, Talent On Board, Talent Development and Talent Retention is used as a reference to analyze each process of talent management practices that are run. The results show that Talent Management in the division card collection of PT. Bank Mega Semarang produces individual talent for regeneration in leadership, but there are still employees who resign before the contract expires. In the Talent Acquisition and Talent Retention stage it has not been effective.